Worldwide Research Trends on Artemisinin: A Bibliometric Analysis From 2000 to 2021 - Dong, Yankai; Liu, Lina; Han, Jie; Zhang, Lianqing; Wang, Yi; Li, Juan; Li, Yuexiang; Liu, He; Zhou, Kun; Li, Luyao; Wang, Xin; Shen, Xue; et al. (Frontiers in Medicine, 2022)
Background and Objective: Artemisinin is an organic compound that comes from Artemisia annua. Artemisinin treatment is the most important and effective method for treating malaria. Bibliometric analysis was carried out to identify the global research trends, hot spots, scientific frontiers, and output characteristics of artemisinin from 2000 to 2021. Methods: Publications and their recorded information from 2000 to 2021 were retrieved through the Web of Science Core Collection (WoSCC). Using VOSviewer and Citespace, the hotspots and trend of studies on artemisinin were visualized. Results: A total of 8,466 publications were retrieved, and for the past 22 years, the annual number of publications associated with artemisinin kept increasing. The US published most papers. The H-index and number of citations of the US ranked first. The University of Oxford and MALARIA JOURNAL were the most productive affiliation and journal, respectively. A paper written by E.A. Ashley in 2011 achieved the highest global citation score. Keywords, such as “malaria,” “artesunate,” “plasmodium-falciparum,” “in-vitro,” “artemisinin resistance,” “plasmodium falciparum,” “resistance,” and “artemether-lumefantrine,” appeared most frequently. The research on artemisinin includes clinical research and animal and cell experiments. Conclusion: The biosynthesis, drug resistance mechanism, and combination of artemisinin have become more popular than before. Studies on artemisinin treating COVID-19 has been carried out, and good research results have been obtained.